Pendekatan Perspektif Weber terhadap Tindakan Rasionalisme Pembuatan Perahu Pinisi - Diah Retno Dwi Hastuti; Mardia Mardia; Dewi Marwati Nuryanti; Muhammad Saleh Ali; Eymal B. Demmalino; Rahmadanih Rahmadanih (Indonesian Journal of Fundamental Sciences, 2018)
Indonesia's maritime triumph from history to being written in a song lyric is not a question, especially its reliability in making Pinisi boats whose processes are full of local wisdom and cultural values reflected in everyday life. The research conducted in Bira Village, Bontobahari Sub-district, Bulukumba District in            May 2018 aims to examine the rationalism of making pinisi boats with Weber's perspective approach. The aim is to use qualitative methods with Weber's approach in the verstehen perspective. The findings show that the making of the Pinisi boat is still filled with mystical nuances of religion ranging from the determination of the day of manufacture to its launch in the sea even though the elements of modernization began to come in to streamline time and streamline costs as a form of rationality in acting, as in Weber's perspective, zwerk rational, werk rational, affectual action, and traditional actions